Influence of Axial Load and a 45-Degree Flexion Head Position on Cervical Spinal Stiffness in Healthy Young Adults - Hofstetter, Léonie; Häusler, Melanie; Schweinhardt, Petra; Heggli, Ursula; Bron, Denis; Swanenburg, Jaap (Frontiers in Physiology, 2021)
Background: Neck pain is a major cause of disability worldwide. Poor neck posture such as using a smartphone or work-related additional cervical axial load, such headgear of aviators, can cause neck pain. This study aimed at investigating the role of head posture or additional axial load on spinal stiffness, a proxy measure to assess cervical motor control. Methods: The posterior-to-anterior cervical spinal stiffness of 49 young healthy male military employees (mean (SD) age 20 ± 1 years) was measured in two head positions: neutral and 45-degree flexed head position and two loading conditions: with and without additional 3 kg axial load. Each test condition comprised three trials. Measurements were taken at three cervical locations, i.e. spinous processes C2 and C7 and mid-cervical (MC). Results: Cervical spinal stiffness measurements showed good reliability in all test conditions. There was a significant three-way interaction between location × head position × load (F(2/576) = 9.305, p < 0.001). Significant two-way interactions were found between measurement locations x loading (F(2/576) = 15.688, p < 0.001) and measurement locations x head position (F(2/576) = 9.263, p < 0.001). There was no significant interaction between loading x head position (F(1/576) = 0.692, p = 0.406). Post hoc analysis showed reduction of stiffness in all three measurement locations in flexion position. There was a decrease in stiffness in C2 with loading, increase in stiffness in C7 and no change in MC. Discussion: A flexed head posture leading to decreased stiffness of the cervical spine might contribute to neck pain, especially if the posture is prolonged and static, such as is the case with smartphone users. Regarding the additional load, stiffness decreased high cervical and increased low cervical. There was no change mid cervical. The lower spinal stiffness at the high cervical spine might be caused by capsular ligament laxity due to the buckling effect. At the lower cervical spine, the buckling effect seems to be less dominant, because the proximity to the ribs and sternum provide additional stiffness.